Knowledge, confidence, and reported behaviors that promote safe water drinking among women of reproductive age - Gergana Damianova Kodjebacheva; Gergana Damianova Kodjebacheva; Lisa M. Lapeyrouse; Jennifer Okungbowa-Ikponmwosa; Loretta Walker; Kanday Campbell; Suzanne Cupal (Frontiers Media S.A., 2023)
IntroductionDrinking lead contaminated water during pregnancy is associated with infant mortality. All women of reproductive age are advised by health agencies to adhere to healthy behaviors due to the chance of unintended pregnancy. Our objectives are to understand knowledge, confidence, and reported behaviors that promote safe water drinking and prevent lead exposure among women of reproductive age.MethodsA survey among females of reproductive age from the University of Michigan - Flint was administered. A total of 83 females who wished to become pregnant one day participated.ResultsLow levels of knowledge, confidence, and reported preventative health behaviors related to safe water drinking and lead exposure prevention existed. Specifically, 71.1% of respondents (59 of 83) were not at all or were somewhat confident in their ability to choose an appropriate lead water filter. Most participants rated their knowledge on how to decrease exposure to lead during pregnancy as poor/fair. No statistically significant differences were detected between respondents residing inside and outside of the city of Flint, Michigan for most variables assessed.ConclusionWhile the small sample size is a limitation, the study adds to an area of scarce research. Despite widespread media attention and resources directed toward reducing the negative health effects of lead exposure following the Flint Water Crisis, significant gaps in knowledge related to safe water drinking remain. Interventions are needed to increase knowledge, confidence, and healthy behaviors that promote safe water drinking among women of reproductive age.